Kemampuan Siswa Kelas IV SD Negeri 6 OKU Membaca Pantun Anak dalam Pembelajaran Bahasa Indonesia - Awalludin Awalludin; Rita Nilawijaya; Tri Riya Anggraini (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2025)
The purpose of this study is to describe the ability of fourth-grade students of SD Negeri 6 OKU to read children's pantun in Indonesian language learning. The method used in this study is a descriptive method. The data collection technique used in this study is a children's pantun reading test. The analysis technique is carried out through a children's pantun reading test. The population and sample amounted to 24 students, through the children's pantun reading test, it turned out that students who got a score of 66-100 were 16 students or 66.66%. While students who got a score of less than 66-100 were 8 students or 33.33%. Thus, it can be concluded that fourth-grade students of SD Negeri 6 OKU are able to read children's pantun in Indonesian language learning. Suggestions for Indonesian language teachers can make children's pantun as an alternative to teaching pantun that will be delivered to students at school in order to increase student motivation so that students are able to improve their skills in reading children's pantun. Students should be more diligent in learning Indonesian, especially when learning about pantun, so that their knowledge of pantun is more developed. Other researchers are advised to conduct further research on pantun, such as how to write pantun, listen to pantun, and so on.